CORRECTION : ASSESSING IN-SITU SEMI-NATURAL BUTTERFLY BREEDING APPROACH OF ORNITHOPTERA CROESUS (PAPILIONIDAE) ON BACAN ISLAND, MALUKU UTARA, INDONESIA - Djunijanti Peggie; Duncan Neville; Sarino Sarino (BRIN Publishing (Penerbit BRIN), 2022)
In the article “ASSESSING IN-SITU SEMI-NATURAL BUTTERFLY BREEDING APPROACH OF ORNITHOPTERA CROESUS (PAPILIONIDAE) ON BACAN ISLAND, MALUKU UTARA, INDONESIA” byDjunijanti Peggie, Duncan Neville, Sarino, and SihKahono (Treubia, 48(1): 55–68, June 2021. http://dx.doi.org/10.14203/treubia.v48i1.4129), there was a terrible mistake in using the subspecies name of lydius(Felder & Felder, 1865) instead of croesus Wallace, 1859 throughout the article. Herewith I would like to apologize for the mistake and would like to clarify that: Ornithoptera croesus lydius (Felder & Felder, 1865) distributes in Halmahera, North Maluku Ornithoptera croesus croesus Wallace, 1859 distributes in Bacan, North Maluku Ornithoptera croesustoeantei Parrot & Schmid, 1984 distributes in Morotai For the purpose of avoiding further misleading information, we would replace the pdf of the article with the correct one provided here. Thank you for your understanding and we will make sure that it will not happen again.